2014
DOI: 10.1007/s10897-014-9790-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism Long‐Term Follow‐up Project: Navigating the Rough Waters of a Multi‐Center, Multi‐State Public Health Project

Abstract: The Region 4 Midwest Genetics Collaborative, made up of seven regional states (Illinois, Indiana, Kentucky, Michigan, Minnesota, Ohio, and Wisconsin), brought together pediatric endocrinologists, state laboratory experts, public health follow-up specialists, and parents of children with congenital hypothyroidism (CH) to identify the three-year follow-up management and education patterns of primary care clinicians and pediatric endocrinologists in the care of children diagnosed with CH by state newborn screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…A total of 409 children were identified in Region 4 as having been diagnosed with CH in 2007 [ 7 ]. The combined birth prevalence was 1:1836 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 409 children were identified in Region 4 as having been diagnosed with CH in 2007 [ 7 ]. The combined birth prevalence was 1:1836 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, 409 children in our region were confirmed to have CH, indicating a birth prevalence of 1:1836 (range, 1:1472–2438). As noted in our previous report outlining the various logistical, regulatory, and legal challenges encountered during this study preparation and execution, we identified a number of methodologies and variables potentially influencing the state differences in birth prevalence [ 7 ]. These included state demographic differences, testing methods, and state-specific cutoff values, along with influences on diagnostic sensitivity, such as sample timing, gestational age, weight of the infant, use of certain therapies, such as blood products, and infant co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations